User Acceptance of the Human Resource Information System: A Study of a Private Hospital in Malaysia - Kamaludin, Kamilah; Kamaludin, Kamil Zaki (International Review of Management and Marketing, 2017)
Technological acceptance and usage is a critical concern as substantial investments are made implementing new information systems. Ipoh Specialist Hospital (ISH) adopted the Human Resource Information System (HRIS) to better manage its human resource functions. Nonetheless, low usage levels have alerted top management that the system may have failed its intended purpose. Thus, this study aims to understand the underlying factors that influence user acceptance of the HRIS at the hospital. Using the Technological Acceptance Model (TAM), we found relations between the following TAM constructs: (1) perceived ease of use, (2) perceived usefulness, (3) information quality, (4) social influence and (5) user satisfaction with system usage. Data from 267 users of the HRIS at ISH show that usage is influenced by perceived ease of use, information quality and social influence towards the system. Surprisingly, perceived usefulness was found to be inversely related to usage. Lastly, system usage was found to influence user satisfaction rather than the other way around. Our findings support management's wariness about the lack of acceptance of the HRIS at ISH. Our study bridges a gap in the human resource management literature and contributes to the application of the TAM in the context of Malaysian healthcare environment, which has thus far been scarce. Keywords: Human Resource Information System (HRIS), Technological Acceptance Model (TAM), organisational change JEL classifications: C2, M150, M500, O330